2017
DOI: 10.1021/acsami.6b15710
|View full text |Cite
|
Sign up to set email alerts
|

Large Grain-Based Hole-Blocking Layer-Free Planar-Type Perovskite Solar Cell with Best Efficiency of 18.20%

Abstract: There remains tremendous interest in perovskite solar cells (PSCs) in the solar energy field; the certified power conversion efficiency (PCE) now exceeds 20%. Along with research focused on enhancing PCE, studies are also underway concerning PSC commercialization. It is crucial to simplify the fabrication process and reduce the production cost to facilitate commercialization. Herein, we successfully fabricated highly efficient hole-blocking layer (HBL)-free PSCs through vigorously interrupting penetration of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 57 publications
5
72
1
Order By: Relevance
“…While for ETL-free device, ETL is absent and the contribution of ETL to J-V hysteresis no longer exists. [93] While, for the mesoscopic PSC without ETL as reported by Han and co-workers, there were almost no substantial hysteresis effects observed as a very small hysteresis index of 0.014 was calculated, which is in accordance with the photoresponse behavior of the mesoscopic PSC with ETL ( Figure 18b). From Figure 18, the device structure, scanning rate, interface modification layer, and HTL specifically adopted all have effect on the hysteresis behavior.…”
Section: Hysteresissupporting
confidence: 88%
See 4 more Smart Citations
“…While for ETL-free device, ETL is absent and the contribution of ETL to J-V hysteresis no longer exists. [93] While, for the mesoscopic PSC without ETL as reported by Han and co-workers, there were almost no substantial hysteresis effects observed as a very small hysteresis index of 0.014 was calculated, which is in accordance with the photoresponse behavior of the mesoscopic PSC with ETL ( Figure 18b). From Figure 18, the device structure, scanning rate, interface modification layer, and HTL specifically adopted all have effect on the hysteresis behavior.…”
Section: Hysteresissupporting
confidence: 88%
“…As the cost of FTO electrodes make up a large portion of the material cost of PSCs, recycling them can also reduce the fabrication cost. [93] They found that the performance of TiO 2 based device was dramatically decreased after only one cycle, which was ascribed to the existence of residual PbI 2 on the TiO 2 surface, whereas the ETL-free device performance was equally maintained with that of the initial cell after four cycles (Figure 19f-h). [93] They found that the performance of TiO 2 based device was dramatically decreased after only one cycle, which was ascribed to the existence of residual PbI 2 on the TiO 2 surface, whereas the ETL-free device performance was equally maintained with that of the initial cell after four cycles (Figure 19f-h).…”
Section: Recyclabilitymentioning
confidence: 98%
See 3 more Smart Citations